Intertidal pools as alternative nursery habitats for coastal fishes - Dias, Marta (2019)
Fish were sampled monthly in four tidal pools, for two years, on the west Portuguese coast. Species diversity of transient fish was higher than that found in previous studies, in other parts of the world. The transient fish population comprised six species: the white seabream, Diplodus sargus, sand smelt, Atherina spp., the thinlip grey mullet, Liza ramada, the Baillon’s wrasse, Symphodus bailloni, the zebra seabream, Diplodus cervinus and the European pilchard, Sardina pilchardus. Abundance varied seasonally, yearly, and among pools, with peak numbers in spring and summer. The most abundant species in all pools, both as larvae and juveniles, was D. sargus. Diplodus sargus and Atherina spp. were present in most pools, from spring to autumn, while rare species were present mostly in the spring-summer period. Smaller mean sizes of larvae and juveniles were observed at the beginning of spring of 2011 (March–April) and at the end of spring/beginning of summer of 2012 (May–June). Mean size of larvae and juveniles often showed a continuous increase from spring to autumn in both years. The highest density peaks were due to the high number of post-larvae entering the pools in spring. In most pools, the overall condition (Fulton’s K) of D. sargus increased throughout the year, in both years. The species richness, the high densities of early stages, and their continuous growth observed in tidal pools strongly emphasize the importance of these environments for larvae and juveniles of several transient marine fishes.